Sosialisasi Pentingnya Persiapan Studi Lanjut Atau Bekerja Sebelum Kelulusan Bagi Siswa Smk (Smkn 2 Yogyakarta) - Mukasi Wahyu Kurniawati; Zeni Ulma (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The socialization of the importance of advanced study preparation or employment before graduation for Vocational High School (SMK) students aims to provide profound understanding and strong motivation to students on the brink of graduation. The objective is to enable them to make meticulous and insightful assessments, leading to wise decisions about their educational trajectory, either in higher education or entering the professional world. This informative session takes place at State Vocational High School 2 Depok and is attended by students from the Petroleum and Petrochemical Processing Techniques (TPMP) department in grades 11 and 12. The well-executed event adheres to the predetermined plan and utilizes methods involving information dissemination and interactive discussions to engage participants in the targeted subject matter. The outcomes of this initiative involve an enhanced comprehension of the conveyed material and the cultivation of a robust motivational spirit within participants. The aim is to prepare them for the choices they will make after completing their education, encompassing the possibility of continuing studies at tertiary institutions or entering the workforce. Furthermore, participants gain a clearer insight into the steps involved in determining a career field that aligns with their interests and abilities, as well as choosing a college major that resonates with their competencies.